Circulating and Excreted Corticosteroids and Metabolites, Hematological, and Serum Chemistry Parameters in the Killer Whale (Orcinus orca) Before and After a Stress Response - Steinman, K. J.; Robeck, T. R.; Fetter, G. A.; Schmitt, T. L.; Osborn, S.; DiRocco, S.; Nollens, H. H.; O’Brien, J. K. (Frontiers in Marine Science, 2020)
Comparisons of circulating and excreted corticosteroid profiles during a biological stress response could provide more data concerning the timing and magnitude of acute hormone changes in different sample matrices. A stress test was performed in 13 zoo-based killer whales (Orcinus orca) whereby animals were elevated out of the water on a rising lift-bottom platform for 20 min. Paired blood and feces were tested for cortisol, corticosterone, aldosterone, and their metabolites and hematological and serum chemistry parameters. Circulating corticosteroids significantly increased during the stress test and returned to pre-treatment concentrations within 24 h, indicating hypothalamic-pituitary-adrenal-axis activation. Concentrations of fecal corticosteroid metabolites did not change significantly during the stress test. Significant differences between pre-test levels and the stress test stage were observed for counts of white blood cells and absolute neutrophils, consistent with a stress leukogram. For serum chemistry, significant deviations from baseline levels were seen for the majority (20/37) of measured parameters. This study provides a direct measurement of the physiologic response of clinically healthy killer whales to a stress event. However, due to the lack of significant changes in fecal hormone metabolite profiles, further investigation of the excretory dynamics of corticosteroids during acute and chronic stress is warranted.